Density functional studies of small Au clusters adsorbed on α-FeOOH: Structural and electronic properties - Fortunato, Leandro Federico (2016)
We report a density functional theory (DFT) investigation on the interaction of tiny Aun (n = 1–5) clusters with the bare and hydroxylated (110) surfaces of goethite (α-FeOOH). Both adsorption and atom-by-atom nucleation processes were modeled. The adsorption is shown to be strong on the bare surface and takes place preferentially through the interaction of Au atoms with unsaturated surface oxygen anions, accompanied with an electronic charge transfer from the metal to the support. Au3, Au4 and Au5 planar structures resulted to be particularly stable due to polarization effects; indeed, Coulombic repulsion between basal Au atoms and surface oxygen anions promotes the displacement of the electronic density toward terminal Au atoms producing a Au+δ(basal)/Au−δ(terminal) polarization. On the hydroxylated surface, Au clusters adsorb more weakly with respect to the bare surface, mainly through monocoordinated surface hydroxyl groups and tricoordinated oxygen ions. Concerning the nucleation mechanism, while on the hydroxylated surface the nucleation energy is governed by the spin of the interacting systems, on the bare surface polarization effects seems to play a predominant role.